Nutritional Status Influences High-Molecular Weight (HMW) Adiponectin levels in Breast Cancer Patients: Comparison with Healthy Controls - Abd Rashid Ainaa Almardhiyah; Zahali Zunura’in; Venkata Murali Krishna Bhavaraju; Siew Hua Gan; Abdullah Sarimah; Syed Abdullah Sharifah Zahhura; Jan Mohamed Hamid Jan (World Nutrition Journal, 2019)
Introduction: Breast cancer is the leading killer of women in Malaysia. Nutritional status and adiponectin are modifiable risk factors for breast cancer occurrence which can be efficiently targeted. The purpose of this study was to determine the relationship between nutritional status and high molecular weight (HMW) adiponectin levels among breast cancer patients as compared to controls. Methods: This was a case- control study, conducted in Hospital Universiti Sains Malaysia and Universiti Sains Malaysia campus. Newly diagnosed breast cancer cases (n=55) were assigned as cases while healthy controls (n=58) were staff members of HUSM and USM campus. Sociodemographic and reproductive data were obtained with a standard questionnaire while the dietary data was obtained from a validated diet history questionnaire. Anthropometric assessments [weight, height, hip, waist circumference (WC) and body fat composition] were measured while overnight fasting venous blood samples were analysed for lipid profiles, glucose, insulin, high sensitivity C-reactive protein and HMW adiponectin. Results: A significant linear negative relationship exists between WC and HMW adiponectin (β=-0.05; p=0.005) among breast cancer cases. Additionally, HDL cholesterol was positively associated with HMW adiponectin (β=1.83; p=0.010) among the cases. BMI was negatively associated with HMW adiponectin (β=-0.02; p=0.001) among healthy controls. Conclusion: Our findings suggest that WC, BMI and HDL cholesterol had significant relationship with HMW adiponectin. Low levels of HMW adiponectin, low WC and high HDL levels may be protective against breast cancer